Debbie Brown's 50 Easy Party Cakes - Brown, Debbie (Millers Point Murdoch Books, 2013)
With a cake design to suit the wishes of any child, from animals to boats, castles and characters, Debbie Brown's 50 Easy Party Cakes is a fuss-free guide to creating a fun and delicious centerpiece.
Include Color Illustrations and Index